Therapeutic and prognostic features in myasthenia gravis patients followed in a tertiary neuromuscular diseases center in Turkey - Yaman, Aylin; Kurtuluş Aydın, Fatma (Frontiers in Neurology, 2023)
Introduction In this study, we aim to evaluate the treatment responses and prognostic characteristics of Myasthenia Gravis (MG) patients followed in a tertiary neuromuscular diseases center in Turkey. Methods One hundred seventy four MG patients (between years 2011 and 2022) in Antalya, Turkey were diagnosed, and evaluated on a classification of MG was based on Myasthenia. Gravis Foundation of America (MGFA) clinical classification. Exclusion of other possible diseases in the differential diagnosis and support by beneficial response to treatment with acetylcholinesterase inhibitors were also taken into consideration. Results Mean age of participants was 54.86 (SD = 14.856; min-max = 22–84). Ninety (51.7%) were female. MG was more common in women under the age of 65 (58%) and in men over the age of 65 (64%). Generalized MG was seen in 75.3% of the patients. Anti-AChR positivities were detected in 52.3%, Anti-MuSK positivity in 4.6%, and seronegativity in 22.4%. Thymoma was detected in nearly 9.8% and thymectomy was performed in 28.7 percent. Most of the patients (57.5%) were using corticosteroids. Azathioprine was used by 39% and mycophenolate mofetil by 10.3% of patients. Mortality was higher and disease was more severe in late-onset (>50 years) MG patients (especially in the COVID-19 pandemic). Eight patients (four women, four men, mean age 75.5 years) died during follow-up. None of them died due to myasthenic worsening, two died due to malignancy and two due to infection. During the COVID pandemic, 16 patients (9.2%) had COVID infection. Four patients died due to COVID-19 infection, these four patients had serious comorbidities, and three of them were elderly (>75 years). Conclusion In conclusion, MG is more common in women between the ages of 20–40 and in men over the age of 65. The use of corticosteroids was more common under the age of 50, and the use of non-steroidal immunosuppressant agents was more common over the age of 50. Thymectomy is still an important supportive treatment approach in anti-AChR positive and seronegative generalized patients under 50 years of age. IVIG and plasmapheresis are effective treatments during acute exacerbations and bridging periods of treatments. Specific treatments are needed especially for resistant group of patients.